2015
DOI: 10.1541/ieejjia.4.722
|View full text |Cite
|
Sign up to set email alerts
|

Bridge Inductance of Closed Slot Induction Motor for Design Process

Abstract: In the design of the induction motor, the equivalent circuit is used to predict its performance. The equivalent circuit consists of the magnetizing reactance and iron loss resistance, primary and secondary resistance and primary and secondary leakage reactance.The secondary leakage reactance of the closed slot rotor is not easy to calculate, because the closed slot rotor has a thin magnetic steel sheet bridge, through which the leakage flux passes. The inductance of the bridge changes depending on the B-H char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In Ref. [1], the authors propose a novel design method for the IM by using the calculated B-H characteristics with the equivalent circuit. They showed that the bar currents change from about 4 to 580 A when the slip sifts from 0 to 100%.…”
Section: Considering Materials Characteristics Somementioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [1], the authors propose a novel design method for the IM by using the calculated B-H characteristics with the equivalent circuit. They showed that the bar currents change from about 4 to 580 A when the slip sifts from 0 to 100%.…”
Section: Considering Materials Characteristics Somementioning
confidence: 99%
“…These achievements have been highlighted by many researchers who have proposed novel approaches to improve motor performance. Three groups of topics will be introduced in this paper: optimal design methods [1][2][3][4][5][6][7][8][9], novel motor structures [10][11][12][13][14][15][16], and novel control methods [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%